HISTORY OF INVESTMENT COOPERATION BETWEEN UZBEKISTAN AND THE CHINESE REPUBLICS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
In the article of the Republic of Uzbekistan and China in the middle of the balanced, mutually beneficial cooperation in the sphere of the investment analysis.